2021
DOI: 10.1590/1414-462x202129020474
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do sistema de vigilância epidemiológica da leptospirose em Campinas, São Paulo, 2007 a 2014

Abstract: Resumo Introdução A leptospirose figura na lista de doenças de notificação compulsória no Brasil. Objetivo Avaliar o sistema de vigilância epidemiológica da leptospirose no município de Campinas, São Paulo, no período de 2007-2014. Método Foi realizado um estudo de prevalência dos casos de leptospirose no sistema de vigilância epidemiológica. Foram analisados 2.949 casos notificados, considerando-se os atributos do Updated Guidelines for Evaluating Public Health Surveillance Systems e os parâmetros proposto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
(5 reference statements)
0
3
0
2
Order By: Relevance
“…In Brazil, the epidemiological data of leptospirosis may be nonexistent and inaccurate [ 42 ], given that the often nonspecific or silent clinical presentation of the disease contributes to its underreporting [ 43 ]. Still, it is much more difficult to raise awareness about the need to notify the suspected cases of leptospirosis by health professionals [ 6 , 44 ]. In this context, it was observed that the distribution of leptospirosis incidence rates in Rio Grande do Sul varied greatly in the different regions of the state; in 20 municipalities, it was very high in the evaluated period, while in 220 municipalities, cases the disease was not recorded in the years evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the epidemiological data of leptospirosis may be nonexistent and inaccurate [ 42 ], given that the often nonspecific or silent clinical presentation of the disease contributes to its underreporting [ 43 ]. Still, it is much more difficult to raise awareness about the need to notify the suspected cases of leptospirosis by health professionals [ 6 , 44 ]. In this context, it was observed that the distribution of leptospirosis incidence rates in Rio Grande do Sul varied greatly in the different regions of the state; in 20 municipalities, it was very high in the evaluated period, while in 220 municipalities, cases the disease was not recorded in the years evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…8 For consistency, the considered categories were: excellent, greater than or equal to 90.0%; regular, from 70.0% to 89.9%; and poor, less than 70.0%. 12 The annual percentage change (APC) was calculated using Prais-Winsten linear regression, with the biennium as the independent variable (y) and the percentage of completeness as the dependent variable (x). 13 A significance level of 5% was used in statistical tests and a 95% confidence interval (95%CI) was calculated.…”
Section: Methodsmentioning
confidence: 99%
“… 8 For consistency, the considered categories were: excellent, greater than or equal to 90.0%; regular, from 70.0% to 89.9%; and poor, less than 70.0%. 12 …”
Section: Methodsmentioning
confidence: 99%
“…8 Para a consistência, as categorias consideradas foram: excelente, igual ou superior 90,0%; regular, de 70,0% a 89,9%; e baixa, inferior a 70,0%. 12 A variação percentual anual (VPA) foi calculada utilizando-se a regressão linear de Prais-Winsten, sendo o biênio a variável independente (y) e os percentuais de completitude a variável dependente (x). 13 Utilizou-se o nível de significância de 5% nos testes estatísticos e calculou-se o intervalo de confiança de 95% (IC 95% ).…”
Section: Métodosunclassified